(untitled) (Social and Environmental Law Journal, 2024)
Democracy is seen as the best form of government to be adopted by a country and constitutes a sine qua non condition for these same governments not to be considered international pariahs. From the institutional security attributed to democracy to the full enjoyment of the rights of its citizens, all elements apparently converge to the premise that democracy must be effectively nurtured as an idea and preserved when put into effect. However, its preservation does not have a consensus regarding the forms chosen for this purpose. Should all citizens actively participate in democratic defense? Is it possible to remove elements inherent to democracy, such as political rights, on the grounds that they are not being used in the “correct” way? These questions do not have simple or fixed answers. The premise from which it is based is that democracy is not self-sufficient, therefore, it requires protection that takes into account its incapacity for self-preservation. If this is true, is it possible to act in this political and legal environment that makes up democracy without incurring theoretical and pragmatic mistakes? The research is separated into three distinct moments. Firstly, a theoretical framework regarding democracy will be determined. Secondly, the theory of militant democracy will be presented with some of the arguments that constitute the main concerns for its scholars.